PRELIMINARY REPORT: LAPAROSCOPIC RADICAL PROSTATECTOMY IN JAKARTA - Johan, Mohammad; Mochtar, Chaidir Arif; Umbas, Rainy (Indonesian Urological Association, 2012)
Objective: To report initial experience of laparoscopic radical prostatectomy (LRP) in Jakarta and evaluate the functional and oncology outcome. Material & Method: Between June 2007 until September 2008, we had done 9 times LRP surgery. All data is retrospectively taken and divided in three groups, i.e. pre-operative data (patient demography, pre-operative PSA, prostate volume, Gleason Score, clinical and functional staging), intra-operative data (intra-operative complication, conversion to open surgery, bleeding volume, and operating time), and post-operative data (post-operative complication, duration of urine catheter usage, duration of hospitalization, functional and oncology status). Results: Among nine subjects who underwent LRP, five subjects (55,55%) did not converted into open surgery. There are 2 subjects who gain their sexual potency and urine continence in one year post op. Only one subject is proven without biochemical failure in 1 year. Conclusion: We confirmed that radical prostatectomy can be performed with transperitoneal laparoscopic technique by a team that has been experienced in laparoscopic. Keywords: Laparoscopic radical prostatectomy, functional result, oncological result.